2000
DOI: 10.1162/105474600566871
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into Performance of Minimally Invasive Telesurgery with Feedback Time Delays

Abstract: This paper describes the testbed telesurgery system that was developed in MIT's Human Machine Systems Laboratory. This system was used to investigate the effects of communication time delays on controller stability and on the performance of surgical tasks. The system includes a bilateral force-reflecting teleoperator system, interchangeable surgical tools, audio and video communication between the master and slave sites, and methods to generate time delays between the sites. To compensate for the time delays,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In addition to the necessary coordination related to preparing the robot and specialized instruments, maintaining patient status, and ensuring a smooth flow of the procedure, the remote teams must also coordinate their activities, often with a time lag due to transmission bandwidth limitation [33]. Delays in feedback have been shown to adversely affect the performance and coordination of remote manipulation tasks and communication [34]. Research has suggested that more effective training and evaluation methods, along with a focus on teamwork and communication, may mitigate some of the risks of patient harm in robotic surgery [35][36][37].…”
Section: Communication In Robotic Surgerymentioning
confidence: 99%
“…In addition to the necessary coordination related to preparing the robot and specialized instruments, maintaining patient status, and ensuring a smooth flow of the procedure, the remote teams must also coordinate their activities, often with a time lag due to transmission bandwidth limitation [33]. Delays in feedback have been shown to adversely affect the performance and coordination of remote manipulation tasks and communication [34]. Research has suggested that more effective training and evaluation methods, along with a focus on teamwork and communication, may mitigate some of the risks of patient harm in robotic surgery [35][36][37].…”
Section: Communication In Robotic Surgerymentioning
confidence: 99%
“…An early study by Ferrell [1966] showed that, as with visual feedback, delayed haptic feedback in a positioning task results in an increase in performance time and errors, but the intervals of delay (0.3, 1, 3 s) were not sufficiently small that we can learn about how the user might respond to subtle increases in latency. A study of latency in tele-surgery [Ottensmeyer et al 2000] demonstrated that surgeons are more sensitive to a latency in haptic feedback than in visual when performing a laparoscopy task. However, the levels of latency examined (600 or 1200 ms) were again too large, as well as too few in number, to provide a model of performance.…”
Section: Delayed Feedback In Single-user Virtual Environmentsmentioning
confidence: 99%
“…While the low level layer provides a consistent, low latency infrastructure for buffering messages to and from multiple remote locations, the higher level layer [9] builds on top of this to provide a hierarchical topology for Distributed Virtual Environments (DVEs). This topology assumes that the environment is split into domains and controls the individual users in these domains.…”
Section: Application Developmentmentioning
confidence: 99%
“…The users experience and sense of immersion would be enhanced and would complement the visual display only if both the haptic and the visual feedback are consistent with each other. Evidence show that latency is a limiting factor in shared haptic environments [9]. Latency creates a lag from when collision is detected and when a force is applied to the display device.…”
Section: Introductionmentioning
confidence: 99%